Pengembangan Media Pembelajaran Interaktif Berbasis Video Animasi Doratoon Pada Pembelajaran Di Kelas V Sekolah Dasar - Rahayu, Listia; Dewi, Ratna Sari; Hakim, Zerri Rahman (Universitas Muhammadiyah Magelang, 2023)
Research on the development of doratoon animated video-based learning media was carried out based on needs at SDN Singarajan, especially in class V, which required novelty or innovation in the use of media in learning, especially digital-based media used by teachers. The research was conducted with the aim of describing the process of developing interactive learning media based on Doratoon animated videos, finding out the feasibility of interactive learning media based on Doratoon animated videos and knowing students' responses to interactive learning media based on Doratoon animated videos. The research method used is the Research and Development (R&D) method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The final results of media validation obtained an assessment of 88.5% in the